DIFFERENCES IN ABNORMAL RETURNS AND TRADING VOLUME ACTIVITY BEFORE AND AFTER THE ANNOUNCEMENT OF THE 2024 PRESIDENTIAL PAIRS IN COMPANIES REGISTERED ON LQ45 - Miftahul Ihsan; Yovita Vivianty Indriadewi Atmadjaja; Ni Made Nadia Suta Pradhani (CV. Radja Publika, 2024)
The aim of this research is to determine the market reaction to the announcement of the 2024 presidential candidate pair which was studied using abnormal returns and trading volume activity. This research uses an event study approach with a 15 day event window. The research sample was based on purposive sampling of 45 companies included in the LQ-45 Index. From the results of the normality test, it is known that there is normally distributed data and data that not normally distributed, so the hypothesis testing method used is the one sample t-test, the one sample Wilcoxon Signed-Rank test and the Wilcoxon Signed Rank Test. The results show (1) There is a difference in abnormal returns both before and after the announcement of the 2024 presidential candidate pair. (2) There is a significant change in trading volume activity both before and after the announcement of the 2024 presidential candidate pair. (3) There is a significant difference in the average abnormal return between the period before and after the announcement of the 2024 presidential candidate pair. (4) There is a significant difference in the average trading volume activity between the period before and after the announcement of the 2024 presidential candidate pair.